Administration of dietary antioxidants for patients with inflammatory bowel disease: A systematic review and meta-analysis of randomized controlled clinical trials - Hossein Shahinfar; Nastaran Payandeh; Maryam ElhamKia; Fatemeh Abbasi; Alireza Alaghi; Farhang Djafari; Masoumeh Eslahi; Narjes Sadat Farizani Gohari; Parivash Ghorbaninejad; Mohaddeseh Hasanzadeh; Alireza Jafari; Aliyu Tijani Jibril; et al. (Elsevier, 2021)
Objective: Accumulating evidence has been reported regarding the effect of dietary antioxidants on clinical variables in IBD patients, however, findings are controversial. This systematic review and meta-analysis aimed to investigate effect of dietary antioxidants on clinical variables in patients with IBD or its subtypes. Methods: We searched PubMed, Scopus, and ISI Web of Science from inception to January 2021 using relevant keywords. Data were pooled by using the random-effect model. All statistical analyses were done using STATA version 14. Results: Our meta-analysis was exclusively done on studies about the effect of curcumin on IBD patients, because limited studies were done on other antioxidants. Curcumin administration resulted in significant increment of clinical remission in patients with IBD (SMD: 0.86%, 95% CI: 0.16, 1.56, p = 0.016), significant remission in clinical symptoms (SMD: −0.96 score, 95% CI: −1.34, −0.57, p < 0.001), and significant increment in endoscopic remission in IBD patients (SMD: 0.51%, 95% CI: 0.16, 0.85, p = 0.004), comparing to control group. Curcumin supplementation also made better clinical response than control group (SMD: 0.74%, 95% CI: 0.22, 1.26, p = 0.005) and also resulted in significant improvement in quality of life of patients with IBD, as compared to control group (SMD: 1.23 score, 95% CI: 0.72, 1.74, p < 0.001). Conclusions: Our meta-analysis showed that curcumin significantly improved clinical and endoscopic remissions in IBD patients. This supplementation also caused significant reduction in clinical symptoms of IBD patients along with better clinical response and the increased quality of life. Further researches with larger sample size and longer period of intervention are required to evaluate efficacy of dietary antioxidants on clinical variables in patients with IBD.